2003
DOI: 10.1182/blood-2002-07-1960
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell lymphomas unspecified presenting in the skin: analysis of prognostic factors in a group of 82 patients

Abstract: In the present study the clinicopathologic and immunophenotypic features of 82 patients with a CD30 ؊ peripheral T-cell lymphoma, unspecified, presenting in the skin were evaluated. The purpose of this study was to find out whether subdivision of these lymphomas on the basis of cell size, phenotype, or presentation with only skin lesions is clinically relevant. The study group included 46 primary cutaneous CD30 ؊ large cell lymphomas and 17 small/medium-sized T-cell lymphomas as well as 17 peripheral T-cell ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
238
5
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(258 citation statements)
references
References 9 publications
7
238
5
8
Order By: Relevance
“…Large cell size determined by flow cytometry has been shown to be an independent predictor of worse outcome in dogs with circulating neoplastic B cells and in dogs with nodal B cell lymphomas 10, 16. Larger cell size has also been associated with worse outcome in human adult T‐cell lymphoma (ATL) and cutaneous PTCL 17, 18. Loss of the surface expression of the pan‐T cell marker CD5 was a relatively common finding within the CD4+/CD45+ lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Large cell size determined by flow cytometry has been shown to be an independent predictor of worse outcome in dogs with circulating neoplastic B cells and in dogs with nodal B cell lymphomas 10, 16. Larger cell size has also been associated with worse outcome in human adult T‐cell lymphoma (ATL) and cutaneous PTCL 17, 18. Loss of the surface expression of the pan‐T cell marker CD5 was a relatively common finding within the CD4+/CD45+ lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the overall median survival was significantly better for the patients with localized disease than for the patients with multifocal skin lesions 5,15 . Furthermore, indolent clinical behavior was associated with stable small lesions (<3 cm), low proliferative activity and an intense CD8 positive lymphocyte infiltration, whereas an aggressive course was associated with rapidly evolving large skin lesions (>5 cm), high levels of proliferation markers and rare CD8 lymphocytes 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemically, CD3 and CD4 are positive, but CD8 and CD30 are negative in the majority of the case, and sometimes this is combined with the loss of the pan T cell markers 1,5,[11][12][13][14] . However, many studies have also reported tumors that are CD8 positive or CD4 negative 1,5,9,11,12 . In addition, many PCSM-TCL cases have shown a rich infiltrate of reactive B cells 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations